L’idée des artistes : Panofsky, Cassirer, Zuccaro et la théorie de l’art - Trottein, Serge (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2012)
What exactly is Idea, the concept whose history Erwin Panofsky investigates in the wake of Ernst Cassirer’s explanation of its “systematic meaning?” Is it still the ancient Platonic Idea, so often invoked, but paradoxically incompatible with art, or is it a new concept, that which fostered the emergence of art theory during the Renaissance? And what relationship does it entertain with the artists’ Idea, another name for disegno, whose definitive theory is found in Federico Zuccaro’s 1607 treatise, the culmination and theoretical finale of the Renaissance? Panofsky, finding it impossible to follow the problematical strand proffered him by Cassirer, leaves us in his Idea with the task of untangling an almost inextricable skein, one from which emerge little by little the contours of another history, a history no longer leading dialectically from Plato to Kant, and from the condemnation of artists and poets to a philosophy of symbolic forms, but, via highly convoluted paths, from the appearance of art theory to the birth of aesthetics.